2022
DOI: 10.1039/d2ce01337a
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial profile of axial nanowire heterostructures in the nucleation limited regime

Abstract: Heterostructured nanowires exhibit unique physical and electronic properties and are most commonly grown by the vapor-liquid-solid mechanism. Some of these properties are related to the interfacial abruptness of the heterointerface...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To this end, the seminal work of Biefeld [ 129 ] remains the only approach to access the behavior of vapor–solid distributions under a varying V/III flux ratio, but this model is restricted to the reaction-limited growth kinetics of epilayers and is not adopted for nanowires. Time-dependent generalizations of compositional models, which are used to model the interfacial abruptness in III–V nanowire heterostructures [ 21 , 111 , 115 , 116 , 127 , 148 ], were beyond the scope of this work (a review can be found, for example, in Ref. [ 142 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the seminal work of Biefeld [ 129 ] remains the only approach to access the behavior of vapor–solid distributions under a varying V/III flux ratio, but this model is restricted to the reaction-limited growth kinetics of epilayers and is not adopted for nanowires. Time-dependent generalizations of compositional models, which are used to model the interfacial abruptness in III–V nanowire heterostructures [ 21 , 111 , 115 , 116 , 127 , 148 ], were beyond the scope of this work (a review can be found, for example, in Ref. [ 142 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleation-limited model was used to describe the VLS growth of self-catalyzed [ 115 ] and Au-catalyzed [ 78 , 114 ] nanowires and nanowire heterostructures [ 115 , 116 ]. In Ref.…”
Section: Liquid–solid Incorporation Modelsmentioning
confidence: 99%
“…This means that unintentional compositional gradients typically form across axial heterostructures, limiting the interfacial width to several atomic planes (hereafter referred to as monolayers, MLs) at best. Successful attempts have been made at improving the interfacial sharpness by employing thinner nanowires, ,, lower growth temperatures, a higher Au concentration in Au-catalyzed nanowires, solid catalysts , or flux pulsing , (i.e., deposition of an element while the growth is temporarily interrupted). Among various material systems, GaAs/Al x Ga 1– x As heterostructures are a distinctively attractive choice for device applications due to their tunable electronic properties in combination with a negligible lattice mismatch between the two materials.…”
Section: Introductionmentioning
confidence: 99%